A Bibliometric Study of Scientific Production on Self-Sovereign Identity - Roberto Albeiro Pava Diaz; Rafael Vicente Paez Mendez; Luis Fernando Niño Vasquez (Ingeniería, 2023)
Context: Self-sovereign identity (SSI) enables the creation of user-centric, privacy-by-design, secure, and decentralized identity-management systems. The aim of this paper is to carry out a bibliometric analysis of the scientific production on SSI during the period 2017-2022. Method: A complete bibliometric analysis of all publications on SSI indexed in Scopus and Web of Science was carried out. A corpus of 143 articles was examined by processing their bibliographic metadata on a bibliometric tool. In order to do this, the Bibliometrix packageand the R programming language were used. Results: A bibliometric characterization of the publications on SSI was obtained for the 2017 − 2022 period. The most important keywords used in these publications were identified, as well as their use tendencies throughout this period. Moreover, the most influential authors in the area and the most relevant publication sources were also identified. Conclusions: The results of the bibliometric analysis show that Lotka’s and Bradford’s laws apply for academic publications on SSI, which means that the most relevant publications in this area are concentrated in a relatively small group of authors and journals. Paul Jenkins, Nitin Naik, Yang Liu and Aijun An were the most impactful authors, and Lecture notes in computer science, Frontiers in blockchain and IEEE were the most influential journals. Finally, the keyword analysis showed that Blockchain, Authentication, Identity management, Electronic document identification systems, and Digital identity are currently the most relevant concepts for SSI.